Lectin activity of homeopathy drugs - G, Jaiswal A (International Multidisciplinary Research Journal, 2013)
Lectins are useful for protective effect of plants which are similar to antibodies. They are also helping in the selective binding of Rhizobia during the initiation of root nodules of legume plants. Homeopathic mother tinctures are used to find out their lectin activities, they are- Arnica montana, Cassia sophara, Caulophullum, Ficus indica, Ficus religiosa, Nux vomica, Solanum xantocarpum, Blata oientalis, Spongia tosta and Urtica urens. Nobody tried for mother tinctures for the purpose of lectin activity, this is a first ever attempt to study the lectin activity to show co-relation with remedial effect.